Investigations of the Solid Electrolyte Interphase Using X‐Ray Photoelectron Spectroscopy In situ Experiment on the Lithium‐Based Solid Electrolyte LiPSON. Issue 3 (4th December 2019) - Michel, Fabian; Becker, Martin; Janek, Juergen; Polity, Angelika
Abstract : Lithium phosphorus sulfuric oxide nitride (LiPSON) is prepared by radio frequency (RF) sputtering using a sputter target with compositions of 50 wt% Li3 PO4 and 50 wt% Li2 SO4 . Knowledge about the present phases at the solid electrolyte–lithium anode interface, the so‐called solid electrolyte interphase (SEI), is achieved by performing an in situ sputtering of metallic lithium on the electrolyte and subsequently measuring the chemical bonding by X‐ray photoelectron spectroscopy (XPS). Information about the SEI is of essential interest to understand the process of lithium‐ion conduction in the half cell. Therefore, the information about the formation of lithium phases in the SEI is crucial. Abstract : Herein, the solid electrolyte interphase (SEI) of lithium phosphorus sulfuric oxide nitride (LiPSON) in contact with metallic lithium is explained. At the interface, new phases are formed, e.g., Li2 S and Li2 O. Information on the formation of SEI is crucial for a better understanding of the performance of LiPSON thin films, e.g., in energy storage devices.